REPORT OF OBSERVATION PROJECT ON "ATMOSPHERIC CIRCULATION AND MATERIAL CYCLE IN THE ANTARCTIC" BY JARE-38 - ヤマノウチ, タカシ; ヒラサワ, ナオヒコ; ハヤシ, マサヒコ; YAMANOUCHI, Takashi; HIRASAWA, Naohiko; HAYASHI, Masahiko (National Institute of Polar Research, 1999)
P(論文) An observation project on "Atmospheric Circulation and Material Cycle in the Antarctic" was started by the 38th Japanese Antarctic Research Expedition (JARE-38). The project aims to understand the atmospheric circulation fields, behavior of minor constituents, and their relations. Extended observations including GPS sondes, radiometers, lidar and aerosol sondes were conducted at Dome Fuji Station and collocated observations at Syowa Station. departmental bulletin paper